Investigating the influence of coaches, trainers, and support staff on athletes' decisions to engage in doping practices - Pathan, Dilawar (International Journal of Multidisciplinary Sciences and Arts, 2024)
Doping remains a critical issue in competitive sports, undermining ethical standards and athletes' health. This study investigates the influence of motivational climates, anti-doping education among support personnel, and moral disengagement on athletes' doping susceptibility. A mixed-methods approach was employed, combining quantitative surveys from 150 athletes and 75 support personnel with qualitative interviews. Quantitative findings revealed that ego-oriented motivational climates significantly increased doping susceptibility, while autonomy-supportive climates reduced it. Additionally, athletes supported by personnel who received anti-doping education demonstrated lower susceptibility to doping. Moral disengagement emerged as a key moderator, with athletes under morally disengaged personnel showing higher doping susceptibility regardless of the motivational climate. Qualitative insights further contextualized these findings, highlighting barriers to fostering autonomy-supportive climates and implementing effective education, including resource constraints and systemic pressures. The study underscores the importance of addressing both psychological and systemic factors to mitigate doping behaviors. These findings align with existing research, emphasizing the need for targeted anti-doping interventions that prioritize education, promote autonomy-supportive environments, and address moral disengagement Policy recommendations include mandatory anti-doping education for all support personnel, tailored interventions to reduce moral disengagement, and organizational reforms to discourage performance-driven pressures. Despite its contributions, the study identifies gaps in understanding systemic factors and the long-term effectiveness of existing interventions, calling for future longitudinal and context-specific research. This research provides valuable insights for advancing clean sport initiatives, offering a pathway to enhance ethical behavior in competitive sports through education, leadership, and systemic change.